The Effect of Interpregnancy Interval on the Recurrence Rate of Spontaneous Preterm Birth: A Retrospective Cohort Study - Koullali, Bouchra; Kamphuis, Esme I.; Hof, Michel H.P.; Robertson, Sarah A.; Pajkrt, Eva; de Groot, Christianne J.M.; Mol, Ben W.J.; Ravelli, Anita C.J. (American Journal of Perinatology, 2017)
Objective We assessed, in women with a previous spontaneous preterm birth, the effect of interpregnancy interval on the subsequent preterm birth rate.Design Retrospective cohort study.Setting A nationwide longitudinal dataset of the the Netherlands Perinatal Registry.Population Women with three sequential singleton pregnancies between 1999 and 2009 and a spontaneous preterm birth <37 weeks in the first pregnancy.Methods We evaluated the impact of interpregnancy interval on the course of the next pregnancies. Antenatal death and/or congenital abnormalities were excluded. Conventional and conditional logistic regression analysis were applied. We adjusted for maternal age, ethnicity, socioeconomic status, artificial reproductive techniques, and year of birth.Main Outcome Measures Outcomes studied were preterm birth <37 weeks, <32 weeks, low birth weight <2500 g, and small for gestational age <10th percentile.Results Among 2,361 women with preterm birth in the first pregnancy, logistic regression analysis indicated a significant effect of a short interpregnancy interval (0–5 mo) on recurrent preterm birth <37 weeks (odds ratio [OR], 2.22; 95% confidence interval [CI], 1.62–3.05), <32 weeks (OR, 2.90; 95% CI, 1.43–5.87), and low birth weight (OR, 2.69; 95% CI, 1.79–4.03). In addition, a long interval (≥60 mo) had a significant effect on preterm birth <37 weeks (OR, 2.19; 95% CI, 1.29–3.74). Conditional logistic regression analysis confirmed the effect of a short interval on the recurrence of preterm birth rate <37 weeks and low birth weight.Conclusion In women with a previous spontaneous preterm birth, a short interpregnancy interval has a strong impact on the risk of preterm birth before 37 weeks and low birth weight in the next pregnancy, irrespective of the type of analysis performed.
Keywords: interpregnancy interval; spontaneous; preterm birth; recurrence risk